Is complete stone removal for choledocholithiasis always necessary in extremely elderly patients?. Issue 1 (30th May 2019) - Okuda, Naoko; Sugimoto, Shinya; Nakamura, Haruka; Hisada, Hirohisa; Temma, Taishi; Hashimoto, Yuki; Hayashi, Satoshi; Ito, Tatsuya; Takami, Mayuko; Oyamada, Jun; Kamei, Akira
Abstract : Background and Aim: Endoscopic stone removal has some complications. Although the life expectancy of elderly patients has increased dramatically worldwide, little information is available on the necessity of complete endoscopic stone removal in extremely elderly patients. This study aimed to evaluate the safety and efficacy of complete endoscopic stone removal in extremely elderly patients. Methods: All extremely elderly patients (>90 years) who underwent endoscopic stone removal for choledocholithiasis at our hospital between January 2012 and January 2017 were retrospectively evaluated. The included patients were divided into complete stone removal and incomplete stone removal groups. Complication rate, overall survival (OS), and disease‐specific survival (DSS) rates were compared between the two groups. Results: Overall, 73 patients were included in this study. The median number of stones was one (range, 0–10) and two (range, 1–12) ( P = 0.043), while the median diameter of the largest stones was 9 (range, 0–27) and 14 (range, 5–46) mm ( P = 0.001) in the complete and incomplete stone removal groups, respectively. During the follow‐up period, OS was 60% and 39% and DSS was 95% and 97% in the complete and incomplete stone removal groups, respectively. Kaplan–Meier analysis found no significant difference in OS and DSS between the two groups ( P = 0.052 and P = 0.646, respectively). Conclusion: Complete stone removal might not always be necessary in extremely elderly patients aged ≥90 years. Abstract : A total of 73 extremely elderly patients (>90 years) who underwent endoscopic stone removal for choledocholithiasis were retrospectively evaluated. The patients were divided into complete stone removal and incomplete stone removal (plastic stent insertion) groups. Kaplan–Meier analysis found no significant difference in overall survival (OS), and disease‐specific survival (DSS) between the two groups.